INFLUENCE OF SOLAR RETROGRADE MOTION ON TERRESTRIAL PROCESSES - Sidorenkov, N. S.; Wilson, Ian (Одеські астрономічні публікації, 2017)
The influence of solar retrograde motion on  secular  minima  of  solar  activity,  volcanic  eruptions, climate changes, and other terrestrial processes is investigated. Most collected data suggest that secular minima of solar  activity,  powerful  volcanic  eruptions,  significant climate  changes,  and  catastrophic  earthquakes  occur around events of solar retrograde motion.